HEALTHCARE FINANCING AND REFORM IN UZBEKISTAN: A CASE STUDY OF SIRDARYA REGION - Mamatkulov B.M.; Khomidov M. N. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This research examines the implementation of state medical insurance mechanisms in Sirdarya Region, Uzbekistan. The study analyzes the current state of the healthcare system, identifies challenges in implementing medical insurance, and evaluates its potential impact on healthcare accessibility, quality, and financial sustainability. The paper proposes recommendations to optimize the insurance scheme, ensuring equitable coverage, efficient resource allocation, and improved health outcomes for the region’s population. By understanding the experiences and lessons learned in Sirdarya, the research contributes to the broader discourse on healthcare financing and reform in Uzbekistan.